PERAN KOMUNIKASI ISLAM DALAM PENYEBARAN DAKWAH DI MEDIA SOSIAL - Fauzi Wirahyuda (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This research discusses the role of Islamic communication in the spread of da'wah on social media, which is increasingly important in the digital age. With the emergence of platforms such as Facebook, Instagram, and YouTube, da'wah is undergoing a transformation from traditional to digital methods, allowing preachers to reach a wider and more diverse audience. This research uses a qualitative method with a library research approach, analyzing various related literature. The results show that social media serves as a strategic tool to spread Islamic messages effectively and relevantly, especially among the younger generation. However, challenges such as the spread of hoaxes and radicalization need to be faced with the implementation of wise communication and digital literacy education. The conclusion of this study highlights the importance of utilizing social media to enhance the understanding and acceptance of Islamic teachings in modern society.